1995
DOI: 10.1152/ajpgi.1995.269.3.g352
|View full text |Cite
|
Sign up to set email alerts
|

Novel model of integration of signaling pathways in rat pancreatic acinar cells

Abstract: Cholecystokinin (CCK) is the major pancreatic secretagogue and acinar cell mitogen. This study was performed to determine by which effector systems CCK regulates tyrosine kinases, phosphatidylinositol (PtdIns) 3-kinase, and phospholipase D (PLD) activities. Pancreatic acini loaded with [3H]myristic acid or [3H]inositol were used to assay PLD and PtdIns 3-kinase. G protein activation with NaF increased particulate and crude cytosolic tyrosine kinase and PLD activities. PLD activation was pertussis toxin sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…Of note, we found that the regulatory effect of PI3-kinase on CCK-induced [Ca 2ϩ ] i responses is observed in a wide range of CCK concentrations. At present, there is conflicting evidence on whether CCK (or carbachol) activates PI3-kinase in pancreatic acinar cells (10,20,46,49,55); alternatively, the role of PI3-kinase in Ca 2ϩ signaling may be permissive in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, we found that the regulatory effect of PI3-kinase on CCK-induced [Ca 2ϩ ] i responses is observed in a wide range of CCK concentrations. At present, there is conflicting evidence on whether CCK (or carbachol) activates PI3-kinase in pancreatic acinar cells (10,20,46,49,55); alternatively, the role of PI3-kinase in Ca 2ϩ signaling may be permissive in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ionomycin, LY-294002, and creatine phosphate were from Calbiochem (La Jolla, CA To gain an insight into the mechanism(s) of this regulation, we first measured the effect of the PI3-kinase inhibitors on [Ca 2ϩ ] i responses to various doses of CCK in isolated rat pancreatic acini. We used concentrations of LY-294002 and wortmannin that have been previously shown to inhibit PI3-kinase-mediated pathways in acinar cells (20,46,49,55). The results in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, PLC activates both PKC and TK (34), and PLA 2 activates PKC (1). When treating bilirubin-stimulated acini with PLC inhibitor U-73122 or PLA 2 inhibitor indoxam, both 1 M U-73122 and 1 M indoxam partially but significantly inhibited bilirubinevoked amylase release (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The supernatant was saved for assay of PKC or TK enzyme activity (cytosolic fraction), while the pellet was further homogenized with 1 ml of ice-cold solution A containing 1% Nonidet P-40 and left on ice for 1 h. The homogenate was centrifuged at 100,000 g for 60 min at 4°C, and the supernatant was taken for assay of PKC or TK enzyme activity (membrane fraction). PKC enzyme activity was measured using an enzyme assay kit, whereas TK enzyme activity was measured as reported previously using poly(L-Glu,L-Tyr) (4:1) as a substrate (34). The reaction mixture in a final volume of 50 l contained 2.5 M Tris ⅐ HCl, 2.5 M MgCl 2, 0.5 nM orthovanadate, 0.02% Triton X-100, 3 nM ATP, 0.4 Ci [␥-32 P]ATP, and 100 g Glu-Tyr polymer.…”
Section: Methodsmentioning
confidence: 99%
“…Previous observations indicated that tyrosine kinases and MAPKs were associated with growth-related processes (31,34). We therefore investigated their potential involvement in MIA PaCa-2 cell growth by measuring their specific activation in response to SS-14 and SMS.…”
Section: Effects Of Ss-14 and Sms On Tyrosine Kinase And Map Kinase Amentioning
confidence: 99%